2022
DOI: 10.3390/healthcare10122368
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Neuropsychiatric Disorders during the COVID-19 Pandemic: Focus on Emotional Well-Being and Parental Stress

Abstract: (1) Introduction: The aim of our research was to explore emotional/behavioral changes in adolescents with neuropsychiatric conditions during the COVID-19 pandemic, and parental stress levels through a standardized assessment, comparing the data collected before and during the first months of lockdown. Moreover, an additional goal was to detect a possible relationship between emotional/behavioural symptoms of adolescents and the stress levels of their parents. (2) Methods: We enrolled 178 Italian adolescents ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…For this reason, we also measured the stress level in parents of children and adolescents with epilepsy to determine if and how parental stress is linked to the condition of their children. According to previous literature data ( 31 33 ) and using PSI as a psychodiagnostics tool, we found statistically significant levels in terms of parenting stress in the study group compared to controls.…”
Section: Discussionsupporting
confidence: 62%
“…For this reason, we also measured the stress level in parents of children and adolescents with epilepsy to determine if and how parental stress is linked to the condition of their children. According to previous literature data ( 31 33 ) and using PSI as a psychodiagnostics tool, we found statistically significant levels in terms of parenting stress in the study group compared to controls.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, in this regard, we should also consider that our study was conducted during the COVID-19 pandemic, and this may have been an additional factor that impacted parental stress [ 30 , 31 , 32 ]. Some recent research showed that the COVID-19 pandemic can be a source of parental stress in parents of children and adolescents with various neuropsychiatric conditions, including epilepsy [ 33 , 34 ]. On the other hand, an observational study by Armeno and colleagues (2022) [ 35 ] did not highlight additional difficulties in managing the KD during the COVID-19 pandemic and supported the feasibility and safety of initiating and managing the KD by telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that neurodevelopmental disorders are related to an increase in parental stress levels [48][49][50][51]. The analysis of change in parental stress over time showed a significant increase in parental stress levels during the first lockdown compared to pre-COVID levels; on the contrary, after 1-year follow-up no significant change in parental stress was found.…”
Section: Discussionmentioning
confidence: 89%